Arduino control of ME 570 motor lab apparatus - Patterson, Eric L (Kansas State University, 2023)
This paper first describes the existing “Motorlab” apparatus that is used for instruction in the Control of Mechanical Systems course, ME 570. It then documents the modification of the afore mentioned Motorlab to accommodate control by Arduino, allowing for full student programmability. A new lab exercise that utilizes Arduino control is then documented, along with the presentation of student reaction to the new exercise.
Keywords: ME 570; Motorlab; Arduino